Inequalities in healthcare disruptions during the COVID-19 pandemic: evidence from 12 UK population-based longitudinal studies. Issue 10 (13th October 2022) - Maddock, Jane; Parsons, Sam; Di Gessa, Giorgio; Green, Michael J; Thompson, Ellen J; Stevenson, Anna J; Kwong, Alex SF; McElroy, Eoin; Santorelli, Gillian; Silverwood, Richard J; Captur, Gabriella; Chaturvedi, Nishi; et al.
Abstract : Objectives: We investigated associations between multiple sociodemographic characteristics (sex, age, occupational social class, education and ethnicity) and self-reported healthcare disruptions during the early stages of the COVID-19 pandemic. Design: Coordinated analysis of prospective population surveys. Setting: Community-dwelling participants in the UK between April 2020 and January 2021. Participants: Over 68 000 participants from 12 longitudinal studies. Outcomes: Self-reported healthcare disruption to medication access, procedures and appointments. Results: Prevalence of healthcare disruption varied substantially across studies: between 6% and 32% reported any disruption, with 1%–10% experiencing disruptions in medication, 1%–17% experiencing disruption in procedures and 4%–28% experiencing disruption in clinical appointments. Females (OR 1.27; 95% CI 1.15 to 1.40; I 2 =54%), older persons (eg, OR 1.39; 95% CI 1.13 to 1.72; I 2 =77% for 65–75 years vs 45–54 years) and ethnic minorities (excluding white minorities) (OR 1.19; 95% CI 1.05 to 1.35; I 2 =0% vs white) were more likely to report healthcare disruptions. Those in a more disadvantaged social class were also more likely to report healthcare disruptions (eg, OR 1.17; 95% CI 1.08 to 1.27; I 2 =0% for manual/routine vs managerial/professional), but no clear differences were observed by education. We did not find evidence that these associations differed by shielding status. Conclusions: Healthcare disruptions during the COVID-19 pandemic could contribute to the maintenance or widening of existing health inequalities.